Glasses and Grains poincarâe seminar 2009 - Duplantier, Bertrand; Halsey, Thomas C.; Rivasseau, Vincent 1955- (Progress in mathematical physics, 2011)
This tenth volume in the Poincaré Seminar Series describes recent developments at one of the most challenging frontiers in statistical physics - the deeply related fields of glassy dynamics, especially near the glass transition, and of the statics and dynamics of granular systems. These fields are marked by a vigorous interchange between experiment, theory, and numerical studies, all of which are well represented by the leading experts who have contributed articles to this volume. These articles are also highly pedagogical, as befits their origin in lectures to a broad scientific audience. Highlights include a Galilean dialogue on the mean field and competing theories of the glass transition, a wide-ranging survey of colloidal glasses, and experimental as well as theoretical treatments of the relatively new field of dense granular flows. This book should be of broad general interest to both physicists and mathematicians.